2012
DOI: 10.1371/journal.pone.0033066
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Evolution of the Vertebrate and Mammalian Selenoproteomes

Abstract: BackgroundSelenium is an essential trace element in mammals due to its presence in proteins in the form of selenocysteine (Sec). Human genome codes for 25 Sec-containing protein genes, and mouse and rat genomes for 24.Methodology/Principal FindingsWe characterized the selenoproteomes of 44 sequenced vertebrates by applying gene prediction and phylogenetic reconstruction methods, supplemented with the analyses of gene structures, alternative splicing isoforms, untranslated regions, SECIS elements, and pseudogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
188
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(200 citation statements)
references
References 88 publications
9
188
1
2
Order By: Relevance
“…The selenoproteins belonging to the GPx family (GPx1-GPx6), Txnrd family (Txnrd1, Txnrd2, and Txnrd3), and the Dio family (Dio1, Dio2, and Dio3) play vital roles in redox regulation, antioxidant defense, the conversion of T4 to T3, and immune regulation in human diseases (Bellinger et al 2009;Pappas et al 2008). Other selenoproteins have also been identified in mammals and chickens, such as SPS2, Seli, Selk, Selm, Sel-15, Sepw1, Selh, Selv, Sepn1, Selo, Sepp1, Seli, Sels, and Selt (Mariotti et al 2012;Novoselov et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selenoproteins belonging to the GPx family (GPx1-GPx6), Txnrd family (Txnrd1, Txnrd2, and Txnrd3), and the Dio family (Dio1, Dio2, and Dio3) play vital roles in redox regulation, antioxidant defense, the conversion of T4 to T3, and immune regulation in human diseases (Bellinger et al 2009;Pappas et al 2008). Other selenoproteins have also been identified in mammals and chickens, such as SPS2, Seli, Selk, Selm, Sel-15, Sepw1, Selh, Selv, Sepn1, Selo, Sepp1, Seli, Sels, and Selt (Mariotti et al 2012;Novoselov et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In chicken, 25 selenoproteins have been identified (Mariotti et al 2012). Selenoproteins are recognized by their different characteristics and functions (Bellinger et al 2009;Pappas et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these newly predicted selenoproteins have been experimentally verified, implying that these computational approaches are highly efficient for selenoprotein identification. Recent comparative genomics analyses also revealed that many of these selenoproteins are widespread in many eukaryotes including both vertebrates and invertebrates (Jiang et al 2012;Mariotti et al 2012).…”
Section: Identification Of Selenoprteins In Platyhelminthes Genomesmentioning
confidence: 99%
“…Thus, we considered them as the most indispensable selenoproteins in animals. Another selenoprotein family, SelR, is also included in this group because SelR is also reported to be present in many phyla of animals, especially all vertebrates (Mariotti et al 2012) . However, the fact that only Cys-containing homologs were found in, platyhelminthes, implying that it may have become selenium-independent in this phylum.…”
Section: Comparison Of Platyhelminthes Selenoproteomes With Other Animentioning
confidence: 99%
See 1 more Smart Citation